High throughput screening of particle conditioning operations: I. System design and method development. Issue 8 (8th May 2015) - Noyes, Aaron; Huffman, Ben; Godavarti, Ranga; Titchener‐Hooker, Nigel; Coffman, Jonathan; Sunasara, Khurram; Mukhopadhyay, Tarit
ABSTRACT The biotech industry is under increasing pressure to decrease both time to market and development costs. Simultaneously, regulators are expecting increased process understanding. High throughput process development (HTPD) employs small volumes, parallel processing, and high throughput analytics to reduce development costs and speed the development of novel therapeutics. As such, HTPD is increasingly viewed as integral to improving developmental productivity and deepening process understanding. Particle conditioning steps such as precipitation and flocculation may be used to aid the recovery and purification of biological products. In this first part of two articles, we describe an ultra scale‐down system (USD) for high throughput particle conditioning (HTPC) composed of off‐the‐shelf components. The apparatus is comprised of a temperature‐controlled microplate with magnetically driven stirrers and integrated with a Tecan liquid handling robot. With this system, 96 individual reaction conditions can be evaluated in parallel, including downstream centrifugal clarification. A comprehensive suite of high throughput analytics enables measurement of product titer, product quality, impurity clearance, clarification efficiency, and particle characterization. HTPC at the 1 mL scale was evaluated with fermentation broth containing a vaccine polysaccharide. The response profile was compared with the Pilot‐scale performance of a non‐geometrically similar, 3 L reactor. An engineering characterization of the reactors and scale‐up context examines theoretical considerations for comparing this USD system with larger scale stirred reactors. In the second paper, we will explore application of this system to industrially relevant vaccines and test different scale‐up heuristics. Biotechnol. Bioeng. 2015;112: 1554–1567. © 2015 Wiley Periodicals, Inc.